A Critical Approach to Social Emotional Learning Instruction Through Community-Based Service Learning. (July 2014) - McKay-Jackson, Cassandra
The traditional teaching of reading, writing, and arithmetic alone will not fully prepare students to lead with integrity, govern fairly, analyze problems, and work collectively with people different from themselves. Social emotional learning (SEL) has been described as one of the missing links in academic education, but a restrictive approach to SEL instruction focuses primarily on emotional and behavioral containment rather than development of active citizenry. Out-of-school programs that provide opportunities for youths to conduct community service learning projects, however, can be a valued resource for supporting critical social emotional learning and social political development. The Chicago Freedom School (CFS) is one such program. This article features the voices of youths' ages 14–16 who participated in CFS during the 2008–2009 Freedom Fellowship, using content analysis. It also discusses future implications for school mental health professionals and SEL instruction.